2014
DOI: 10.1021/tx4004227
|View full text |Cite
|
Sign up to set email alerts
|

Radical Model of Arsenic(III) Toxicity: Theoretical and EPR Spin Trapping Studies

Abstract: Abstract Correspondence to: Frederick. Villamena@osumc.edu , Arsenic is one of the most environmentally significant toxins and a great global health concern. Long known for its acute toxicity, arsenic has also been discovered to be a potent carcinogen. Evidence links arsenic toxicity and carcinogenic actions to reactive oxygen species (ROS). In most animal including humans, arsenic undergoes a biomethylation to yield organic arsenic species, long assumed to be a process of detoxification. However, a growing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 99 publications
1
15
0
Order By: Relevance
“…The intrinsic apoptotic pathway is associated with mitochondrial functions for causing cytochrome c release and activation of caspase‐9, including mtROS . Numerous evidences have shown that ROS play a vital role in DNA damage, cellular apoptosis, tissue damage, and aging . Our results indicated that genistein increased ROS (Figure A) and decreased the levels of Δ Ψ m (Figure C) in HL‐60 cells, thus, we suggesting genistein induced cell apoptosis via ROS and mitochondria.…”
Section: Discussionsupporting
confidence: 51%
“…The intrinsic apoptotic pathway is associated with mitochondrial functions for causing cytochrome c release and activation of caspase‐9, including mtROS . Numerous evidences have shown that ROS play a vital role in DNA damage, cellular apoptosis, tissue damage, and aging . Our results indicated that genistein increased ROS (Figure A) and decreased the levels of Δ Ψ m (Figure C) in HL‐60 cells, thus, we suggesting genistein induced cell apoptosis via ROS and mitochondria.…”
Section: Discussionsupporting
confidence: 51%
“…For example, the EPR spectrum of the HO • radial adduct (DMPO–OH) exhibits signals with a relative peak ratio of 1:2:2:1 with the hyperfine coupling constants of a N = a H = 14.9 G, whereas the EPR spectrum of the HO 2 • radical adduct affords more lines with hyperfine coupling constant of a N (13–14 G) which is significantly larger than a H (9–11 G). 28,3741,47 Carbon-centred radical adducts afford a larger a H value than the a N value. 28,42 Thus, the type of radical species can be readily distinguished based on the hyperfine splitting pattern of the DMPO spin adducts.…”
Section: Resultsmentioning
confidence: 99%
“…-tocopherol, -T) compounds; (2) prevention of radical formation (Halliwell, 1994), such as by ferritin (Ft) action chelating Fe; and (3) repair of already performed damage, such as by the activity of DNA repairing enzymes (Halliwell, 1994). Zamora et al (2014) examined the capacity of trivalent arsenic species arsenous acid (iAs(III)), monomethylarsonous acid (MMA(III)), and dimethylarsinous acid (DMA(III)) to generate ROS through a theoretical analysis of their structures, redox properties, and their reactivities to various ROS using a density functional theory approach and by employing electron paramagnetic resonance (EPR) techniques. Spin trapping studies showed a higher propensity for methylated arsenicals to generate radicals than iAs(III) upon treatment with H 2 O 2 .…”
mentioning
confidence: 99%